2019
DOI: 10.3389/fmicb.2019.01412
|View full text |Cite
|
Sign up to set email alerts
|

Clear Victory for Chlamydia: The Subversion of Host Innate Immunity

Abstract: As obligate intracellular bacterial pathogens, members of the Chlamydia genera are the pivotal triggers for a wide range of infections, which can lead to blinding trachoma, pelvic inflammation, and respiratory diseases. Because of their restricted parasitism inside eukaryotic cells, the pathogens have to develop multiple strategies for adaptation with the hostile intracellular environment—intrinsically present in all host cells—to survive. The strategies that are brought into play at dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 114 publications
0
21
0
Order By: Relevance
“…Epidemiological studies have shown that C. trachomatis infection has also been identified as an independent risk factor of cervical cancer, indicating a potential relationship with HPV infection (Bellaminutti et al, 2014;Di Pietro et al, 2018). In terms of pathogenesis, C. trachomatis is capable of triggering chronic or recurrent infections and long-term inflammations of the urethra (Chen et al, 2019), inducing local secretion of immune mediators, enhancing the production of reactive oxygen species (ROS) and generation of free radicals, which may cause damages to host mucosal barriers and cell-mediated immunity (Conde-Ferraez et al, 2017). These biological effects of C. trachomatis infection could facilitate the transmission and co-infection of HPV and decrease the host's ability to resolve HPV infection.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies have shown that C. trachomatis infection has also been identified as an independent risk factor of cervical cancer, indicating a potential relationship with HPV infection (Bellaminutti et al, 2014;Di Pietro et al, 2018). In terms of pathogenesis, C. trachomatis is capable of triggering chronic or recurrent infections and long-term inflammations of the urethra (Chen et al, 2019), inducing local secretion of immune mediators, enhancing the production of reactive oxygen species (ROS) and generation of free radicals, which may cause damages to host mucosal barriers and cell-mediated immunity (Conde-Ferraez et al, 2017). These biological effects of C. trachomatis infection could facilitate the transmission and co-infection of HPV and decrease the host's ability to resolve HPV infection.…”
Section: Introductionmentioning
confidence: 99%
“…Besides its immune evasion strategies, Chlamydia has evolved an escape to certain stressors by switching to a physiological state in which the bacterium ceases to divide but remains viable, called persistence. We would like to refer to Panzetta et al (2018) and Chen et al (2019) who reviewed the molecular mechanisms Chlamydia employs to counteract host innate immune defenses as well as to establish persistence (Panzetta et al, 2018; Chen et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, OECs responded to these bacteria in a similar manner to macrophages with secretion of a plethora of cyto-and chemokines; the immune response was overall stronger than for trigeminal SCs (Nazareth et al, 2021). Chlamydiae bacteria have previously been widely reported to survive and persist for very long periods in professional phagocytes, in particular in macrophages (reviewed by Chen et al, 2019;Wong et al, 2019). Whether C. muridarum can persist in OECs in the long-term and if this this may contribute to infection of the CNS remains to be investigated.…”
Section: Olfactory Nerves and Infectionmentioning
confidence: 99%